发动机与液力变矩器匹配多目标优化 - 刘俊平; 陈惠贤 (Jixie chuandong)
For the low precision of the matching between engine and hydraulic torque-converter,a method of multi-objective optimization is presented.Based on the relevant characteristic curve,the starting performance,power efficiency and fuel economy are taken as the optimization targets when both of the two are working,multi-objective optimization mathematical model of the matching between engine and torque converter is established.Torque converter loop diameter optimal parameter is deduced through the MATLAB.Finally,a numerical example is given and the optimization results are analyzed.